Examining the Relationship between Supply Chain Relationships and Practice of Distributors (Case Study: NoshinCo) - Mehrmanesh, Hassan; Mirmahalleh, Seyed Rahim Safavi (International Review of Management and Marketing, 2017)
The term "relationships" covers a lot of ground in supply chain management. There are strategic relationships, tactical relationships, transactional relationships, internal relationships, and possibly more. For industrial companies, the last part of the supply chain that is distribution and sale is of great importance duets to its direct relationship with the profit, so they seek to improve the performance of their distributors at the end of the supply chain at any costs. This study aims to investigate the relationship between supply chain relationships and the performance of distributors of manufacturing company, and research methods is descriptive-correlational. The study population is NoshinCo. The results show that there is a significant relationship between relationships in supply chain and the performance of distributors. Keywords: Supply chain, relationships, supply chain, distributors’ performance, NoshinCo JEL Classifications: E37, E32, C53, C5